Angiotensin-converting enzyme, renin-angiotensin system and human performance - Woods, D. (Genetics and Sports, 2009)
The angiotensin-converting enzyme (ACE) I/D polymorphism is strongly associated with circulating ACE levels in European populations. Initial studies over 10 years ago suggested an association between the I-allele (associated with low circulating ACE activity) and elite endurance performance. Subsequent studies also then suggested an association of the D-allele (high circulating ACE) with power-oriented performance. Not all studies are concordant however. The published literature is beset with the problems attendant in interpreting population-association studies including case definition, adequate cohort size, selection bias and appropriate control groups. Notwithstanding this, a plethora of data has been published. This has been followed by various studies trying to elucidate a physiological mechanism for such an association. This chapter will review the available data regarding the ACE I/D polymorphism and human performance both at sea level and at high altitude. It will also evaluate any data pertaining to postulated mechanisms. (Autorreferat)